2012
DOI: 10.7314/apjcp.2012.13.8.4067
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Pioglitazone, a PPAR Gamma Ligand, on Azoxymethane-induced Colon Aberrant Crypt Foci in KK-AуMice

Abstract: Obesity is an established risk factor for colorectal cancer. Pioglitazone is a peroxisome proliferatoractivated receptorγ (PPARγ) agonist that induces differentiation in adipocytes and induces growth arrest and/or apoptosis in vitro in several cancer cell lines. In the present study, we investigated the effect of pioglitazone on the development of azoxymethane-induced colon aberrant crypt foci (ACF) in KK-A y obesity and diabetes model mice, and tried to clarify mechanisms by which the PPARγ ligand inhibits AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Long‐term treatment with long‐acting insulin on C57BL/KsJ‐ db/db mice, which lack a leptin receptor, revealed that insulin increases colonic epithelial cell proliferation, and formation of ACF . Moreover, the anti‐insulin resistant medicine pioglitazone prevented ACF development in KK‐ A y mice through improvement of serum insulin levels, and increase of p27 and p53 mRNA levels in the colorectal mucosa . Hence, it seems likely that hyperinsulinemia in the KK‐ A y and KK mice enhanced the development of AOM‐induced ACF in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term treatment with long‐acting insulin on C57BL/KsJ‐ db/db mice, which lack a leptin receptor, revealed that insulin increases colonic epithelial cell proliferation, and formation of ACF . Moreover, the anti‐insulin resistant medicine pioglitazone prevented ACF development in KK‐ A y mice through improvement of serum insulin levels, and increase of p27 and p53 mRNA levels in the colorectal mucosa . Hence, it seems likely that hyperinsulinemia in the KK‐ A y and KK mice enhanced the development of AOM‐induced ACF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(10)(11)(12) Moreover, the anti-insulin resistant medicine pioglitazone prevented ACF development in KK-A y mice through improvement of serum insulin levels, and increase of p27 and p53 mRNA levels in the colorectal mucosa. (13) Hence, it seems likely that hyperinsulinemia in the KK-A y and KK mice enhanced the development of AOM-induced ACF in the present study. In addition, hyperglycemia and hypertriglyceridemia may also contribute to the development of ACF.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR gamma is also present in other tissues, such as breast [70,71], colon [72][73][74], lung [75,76], ovary [77,78], prostate [79,80] and thyroid [81,82] wherein it mediates several specific functions, such as early development [83], cell proliferation [84], differentiation [85], apoptosis [86], and metabolic homeostasis [87]. Many investigators [88][89][90][91][92][93][94][95][96][97] reported that PPAR gamma was also involved in the control of transcriptional regulation of autophagy.…”
Section: Newly Participant Of Autophagy Regulation: Pparsmentioning
confidence: 99%
“…There is significant evidence from models of diabetes, arthritis, atherosclerosis, Parkinson’s disease, Alzheimer’s disease and others that administration of PPAR natural ligands and synthetic agonists has anti-inflammatory effects. Specific reductions in proinflammatory chemokines and cytokines has been observed in numerous cells types: renal cells (Wang et al, 2011; Lu et al, 2013), vascular smooth muscle cells (Marchesi et al, 2013), adipocytes (Guri et al, 2008; Ueno et al, 2012), mesothelial cells (Sauter et al, 2012), epithelial cells (Neri et al, 2011), splenocytes (Bassaganya-Riera et al, 2011), monocytes/macrophages (Han et al, 2005; Tanaka et al, 2005; Hounoki et al, 2008; Liu et al, 2012), astrocytes (Lee et al, 2008, 2012), and microglia (Kim et al, 2012). …”
Section: Ppar Agonists Can Alter Chemokine Expressionmentioning
confidence: 99%